The ecology of post-Pleistocene peoples on the Gansbaai coast, South Western Cape - Schweitzer, F. R.(Franz Richard) (Stellenbosch : Stellenbosch University, 2012)
Thesis (M.A.) -- University of Stellenbosch, 1975.